Base instability associated with hydraulic uplift in deep excavations in view of Bangkok groundwater rebound - Khachanat Phanomrattanarak; Noppadol Phien-Wej; Pham, Huy Giao; Suttisak Soralump; Royal Thai government scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
Nowadays,Bangkok areas are being congested. There is only limited space in the center of the city. As a result, high-rise buildings are built everywhere and roads and railways are built under the ground which leads to the need of deep excavations. Stability of excavation base is the major considering point. According to the recovering of groundwater, base instability due to hydraulic uplift should be concerned. Thus in this study, the theory related to base instability due to hydraulic uplift is studiedand analyzed by parametric study. The safety factor against hydraulic uplift failure in this study is calculated from Closed Form Solution. The safety factor against shear failure in this study is calculated from Plaxis (2D). By doing the parametric study, we will have better understanding of the effect of each parameteron base stability of excavation. The parameters that will be varied in this study are Undrained shear strength (Cu), Elastic modulus (E), Saturated unit weight ({uF067}), Thickness (T), Groundwater level (U), Length of diaphragm wall (L) and percent of excavation. This study will focus on the result of safety factor against hydraulic uplift and shear failure, vertical displacement at the base, lateral wall movement and ground surface settlement.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Geotechnical and Earth Resources Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2015
Keywords: Groundwater -- Thailand -- Bangkok; Excavation -- Thailand -- Bangkok